Alexander Seton, First Earl of Dunfermline: his library, his house, his world. Issue 3 (21st April 2015) - Davidson, Peter
Abstract This article re-considers Alexander Seton, First Earl of Dunfermline (1555–1622) in his cultural context, particularly in the light of the recently-discovered inventory of his private library. This sophisticated collection of continental books, with strong holdings in art, architecture and Catholic apologetics, offers new information on the intense private Catholicism of a statesman who conformed outwardly to Protestantism. The inventory casts light also on his work of building and decoration at Pinkie House, Musselburgh. The article concludes by raising the possibility of some kind of continuance at Pluscarden Priory in Moray after the reformation and under Seton's protection, and that Seton's daughter Sophia may have built a freestanding Catholic chapel on her marriage to David Lindsay, first Lord Balcarres.